2020
DOI: 10.1371/journal.pone.0237029
|View full text |Cite
|
Sign up to set email alerts
|

The Earth’s magnetic field in Jerusalem during the Babylonian destruction: A unique reference for field behavior and an anchor for archaeomagnetic dating

Abstract: Paleomagnetic analysis of archaeological materials is crucial for understanding the behavior of the geomagnetic field in the past. As it is often difficult to accurately date the acquisition of magnetic information recorded in archaeological materials, large age uncertainties and discrepancies are common in archaeomagnetic datasets, limiting the ability to use these data for geomagnetic modeling and archaeomagnetic dating. Here we present an accurately dated reconstruction of the intensity and direction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…Such data are compared to a geomagnetic secular variation curve, based on synchronization with contemporaneous radiocarbon dates and/or historical records, etc. Since the Earth's magnetic field also varies according to geographical location, a separate calibration curve is needed for different regions 15‐17 . However, detailed secular variation curves for many different regions are not yet well‐defined, and archaeomagnetic dating is often not possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data are compared to a geomagnetic secular variation curve, based on synchronization with contemporaneous radiocarbon dates and/or historical records, etc. Since the Earth's magnetic field also varies according to geographical location, a separate calibration curve is needed for different regions 15‐17 . However, detailed secular variation curves for many different regions are not yet well‐defined, and archaeomagnetic dating is often not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Earth's magnetic field also varies according to geographical location, a separate calibration curve is needed for different regions. [15][16][17] However, detailed secular variation curves for many different regions are not yet well-defined, and archaeomagnetic dating is often not possible.…”
mentioning
confidence: 99%
“…Vaknin et al. (2020) suggested that the LIAA extended at least until 2,536 cal yr BP based on high field intensity values from historically dated burnt structure. This raises a question regarding the timing of the termination of the LIAA.…”
Section: Discussionmentioning
confidence: 99%
“…The VGP path of Caricchi et al (2020) also identified a VGP stand at relatively low latitudes around northern Europe during the early stages of the LIAA, which may explain the high inclinations observed in the Levant before the deposition of the Ein-Feshkha sediments. (Ben-Yosef et al, 2017;Shaar et al, 2011Shaar et al, , 2016Vaknin et al, 2020), Jordan (Ben-Yosef et al, 2009, Syria (Gallet & Al-Maqdissi, 2010;Gallet et al, 2006Gallet et al, , 2008Gallet et al, , 2014Genevey et al, 2003), and Cyprus (Shaar et al, 2015). (b-c) Declination and inclination from EF and from archeomagnetism (Shaar et al, 2018;Speranza et al, 2006;Tema et al, 2018Tema et al, , 2021Vaknin et al, 2020).…”
Section: Implications For Regional Geomagnetic Field Changesmentioning
confidence: 99%
See 1 more Smart Citation